Policing and the idea of democracy - Jones, Trevor (The British journal of criminology, 1996)
This paper has four major objectives. First, through reference to the considerable body of writing on democratic theory, to attempt to clarify what is meant by democracy'. Secondly, to explore the difficulties in applying such concepts to the police service, and to examine how writers of different perspectives have approached this task in the past. Thirdly, to distil a set of democratic criteria' which might be applied to the police service, and finally, to consider the institutional arrangements through which such principles might be applied